Teaching students’ writing skill through Stay and Stray Technique - Putri Rizki; Asnawi Muslem; Dian Fajrina (Research in English and Education Journal, 2017)
The objective of this research was to investigate whether the use of stay and stray technique improved students writing skill in recount text. This study was conducted at State Junior High School 13 (SMPN 13) Banda Aceh. The study used pre-experimental of one group pre-test – post-test design. The sample of this study was class VIII-5 with 21 students, which consists of 13 male and 8 female. The research instrument used in this study was the written test. For pre-test, the students were asked to write a recount text with the topic “memorable day” which consists of 70 words. For the post-test, they were asked to write a recount text with the topic “holiday” which consists of 70 words. The data was collected from the pre-test and post-test result. The data was analyzed by using t-test and statistical formula to prove the hypothesis. The result showed that the students’ mean score in writing result of post-test is better than pre-test, which is 81.3 67. Based on the hypothesis, Ha is accepted since t-test is higher than t-value at the level of significant 0.05 (8.75 2.086). It proves that the use of stay and stray can improve the students’ writing skill in recount text.